Developing a Dynamic Model for Sustainable Development in Yogyakarta City - Didi Nuryadin; Samsubar Saleh; Amirullah Setya Hardi; Evita Hanie Pangaribowo (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
Developments in Yogyakarta City have driven residents of the city and its outskirts to access available social facilities, such as education, healthcare, and employment. If this continues, various social and urban problems may emerge, including increased population density and traffic congestion. Another implication of this process is decreased environmental carrying capacity as a result of continued use of non-sustainable approaches to development. This study aims to model the complexity of the relationships between aspects i.e., social, economic, and environmental of the area studied. The system dynamics method is used, as it is a disciplinary approach that is able to fully explore problems that occur in interconnected systems rather than examining incidents partially. As the basis for this model, the causal loop diagram (CLD) model has been applied based on literature studies and field observations. The result shows that developments in the tourism and education sectors are the main factors affecting the intersections of social, economic, and environmental considerations.